On the Order of the Books in the First Uppsala University Library Building - Sjökvist, Peter (Journal of Jesuit studies, 2019)
Uppsala University Library received several literary spoils of war that had been taken by Swedish armies from Jesuit colleges and other Catholic institutions in the seventeenth century. This article argues that the first university library building in Uppsala, which was built in two floors, kept good and useful literature on the upper floor, where the books were arranged according to faculties, and literature of less use on the lower, where the books were arranged according to a system similar to those in Jesuit libraries. In Lutheran Uppsala, most Catholic literature was therefore located in the lower library. In previous research on this library, its structure has not been fully acknowledged. Hence, several misleading conclusions have been drawn.